Strategi Pengentasan Kemiskinan Dan Pemberdayaan Ekonomi Dengan Filantropi Islam Menjadi Variabel Moderator Terhadap Kesejahteraan Masyarakat : Studi Kasus Yayasan BSM Ummat - Mahathir Muhammad Dewantoro; Fahruddin Salim; Agustinus Miranda (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This 2023 research is entitled Strategy for Poverty Alleviation and Economic Empowerment Using Islamic Philanthropy to Become a Moderating Variable on Community Welfare (Case Study of the BSM UMMAT Foundation). The purpose of this study is to analyze whether there is a significant influence between poverty alleviation and economic empowerment on people's welfare in increasing Muzaki in the future, with Islamic philanthropy as a moderator variable. The success of the Poverty Alleviation and Economic Empowerment Strategy is largely determined by several aspects, namely Capital Assistance, Facilities Development Assistance, Counseling Assistance, Institutional Strengthening, and Strengthening Business Partnerships. The research method used is the correlation and regression method, which is an attempt to measure and test the relationship and forecast of the variables studied, where to test the relationship and predict the variables, namely by using computerized media SPSS, SEM, and Microsoft Excel programs. While the sampling technique used is Non-Probability Sampling/Purposive Sampling which uses a total sample of 50 people. In this entire study, the biggest influence on the t-test is the effect of Economic Empowerment on Islamic Philanthropy (t count of 4.427 is greater than the t-table of 1.96). Economic Empowerment has a positive and significant effect on Islamic Philanthropy. Then, Poverty Alleviation has a positive and significant effect on Islamic Philanthropy, because based on statistical parameters it shows that the t count is 2.045 greater than the t table is 1.96. Economic Empowerment has a positive and significant effect on Community Welfare because based on statistical parameters it shows that t count is 2.698 greater than the t-table of 1.96 and Islamic Philanthropy has a positive and significant effect on Community Welfare because based on statistical parameters it shows that t count is 2.085 greater than t table of 1.96.